Supporting investment projects in the Act on Sureties and Guarantees (ASG) granted by the State Treasury (ST) and certain legal entities – analysis of selected issues - Wojciech Bożek (Prawo Budżetowe Państwa i Samorządu)
The paper discusses a significance of guarantees and sureties granted by the State Treasury and Bank Gospodarstwa Krajowego (BGK) within the framework of governmental guarantee and surety schemes covering projects implemented with the use of the European Union funds. The aim of the study is to determine whether the legislator adjusts the provisions of the currently effective Act of 8 May 1997 on Sureties and Guarantees granted by the State Treasury and certain legal entities to the economic needs of the state, including those related to obtaining funds from the European Union for the implementation of undertakings and projects. It has been assumed that the analysed sureties and guarantees of the State Treasury and BGK have constituted an important and practically applied instrument of economic development of the state for several decades. In the final conclusions, the Author states, among others, that the discussed solutions of the ASG are conducive to supporting an innovative, investment and development activity in the state. However, only the sureties and guarantees of BGK are an effective tool of obtaining the European Union funds which are related to the governmental surety and guarantee scheme. The Author has used a dogmatic and analytical research method, based on the legal status in force on 15 November 2019. Certain aspects of the historical method are evidenced by considerations on the evolution of the solutions adopted in the ASG.